Corporate vs. Free Lifestyle: Tension and Resolutions - Liu, Hsin-Yi (2006)
The issue of how to balance work and leisure activity has been widely debated both in industry and academia. Working people, especially females, are faced with challenges at work as well as in the home. More and more females are entering the workforce; as a result they have to play multiple roles in the high-pressure modern society. Maintaining the well being is of strategic importance to a company in terms of work efficiency, employee morale, turnover and company profitability (Baldiga 2005) Despite the wide recognition of the importance of maintaining a healthy balance of employees work and life balance, it is somewhat surprising to find a relatively small amount of literature that addresses the core of the problem in this area. Of the limited literature, very few solutions have been proposed of any significant value. Even when some family-friendly companies allow practices such as flexible working time and childcare leave, few employees take advantage of these policies. The original aim of this research was to investigate solutions to solve the work/life conflict for professional women, but after an extensive review of published literature and empirical studies on the subject, the conclusion was reached that the reconciliation of work and life balance is extremely difficult and to a large extent depends on individuals personalities, expectations and perceptions. If a female wants to advance in her career and expects great achievements then she probably has to accept the sacrifice she makes with her family. If she perceives non-work life is more important, she may risk being considered as not a serious player in the company (Anat Arkin 1997). The author has conducted interviews and focus groups with middle-aged professional women and concluded those females personalities, expectations and perceptions of their family and career shape the ways they balance their work and life.